Business and nonproliferation industry's role in safeguarding a nuclear renaissance - Banks, John P.; Ebinger, Charles K. (Brookings Institution Press, 2011)
"Forecasts pressure on the fragile nuclear nonproliferation regime because of expected increases in civilian nuclear power nationwide due to global demand and concerns over energy security and greenhouse gas emissions and addresses how the nuclear industry can act as a responsible partner in preventing nuclear weapons proliferation"--Provided by publisher.